Pengaruh Harga, Lokasi, Dan Kualitas Bangunan Terhadap Kepuasan Konsumen Pada Perumahan Bersubsidi Pesona Indah Betung - Hardiansyah; Rabin Ibnu Zainal; Riri Hanifa; Noprian (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
The house is a basic need in the form of a building that functions as a residence or place to live and a means of gathering a family. Housing is a very important need for society. The products offered by developers to consumers must of course be oriented to consumer needs and consumer satisfaction. Research on the effect of price, location and building quality on customer satisfaction in Pesona Indah Betung housing has been conducted in July 2023. The purpose of this study was to analyze the price, location and quality of buildings in Pesona Indah Betung housing on customer satisfaction. The research method used is Multiple Linear Regression. Methods of data collection using questionnaires, interviews and documentation. The number of respondents was 108 people. The results of this study hypothetically t are price and location have a positive effect on customer satisfaction, while building quality has a negative effect on customer satisfaction. The results of the Multiple Linear Regression test for price and location variables have a positive effect on customer satisfaction, while building quality has a negative effect on customer satisfaction in Pesona Indah Betung housing.